Awareness of Risk Factors and Complications of Hypertension in Southern Tanzania - Kanuda Mandago; Fabian P. Mghanga (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: To assess patient’s awareness on the risk factors, complications and prevention of complications of hypertension. Methods: This cross-sectional study was carried out on a random sample of hypertensive patients attending Songea Regional Referral Hospital, Tanzania using an interview based questionnaire. Data entry and analysis was performed using SPSS v 14. Results are expressed as Mean ± SD for continuous data and proportions for categorical data. Logistic regression was performed to assess the association between variables and patients’ awareness on risk factors, complications and prevention of complications of hypertension. Results: Four hundred and fifty hypertensive patients with mean age 57.00±12.60 years were enrolled in the study. Females accounted for 52.90% of the study population. More than one-third (35.60%) of patients had low level of awareness on the risk factors, complications and preventive measures of complication of hypertension. Having higher education level, duration with hypertension of more than 5 years, and a positive family history of hypertension were all associated with high level of awareness among hypertensive patients. Conclusions: The findings show a considerable number of hypertensive patients are not aware of the risk factors, complications and preventive measures of hypertension. Assessing patients’ awareness of risk factors and complications of hypertension during follow-up visits may improve patients’ control of blood pressure and slow down progression to complications.